The long game ebook - Armas, Elena (Green Oak, 2023)
A NEW YORK TIMES BESTSELLER A disgraced soccer exec reluctantly enlists the help of a retired soccer star in coaching a children's team in this small-town love story in the vein of It Happened One Summer —from the New York Times bestselling author of The Spanish Love Deception . Adalyn Reyes has spent years perfecting her daily routine: wake up at dawn, drive to the Miami Flames FC offices, try her hardest to leave a mark, go home, and repeat. But her routine is disrupted when a video of her in an altercation with the team's mascot goes viral. Rather than fire her, the team's owner—who happens to be her father—sends Adalyn to middle-of-nowhere North Carolina, where she's tasked with turning around the struggling local soccer team, the Green Warriors, as a way to redeem herself. Her plans crumble upon discovering that the players wear tutus to practice (impractical), keep pet goats (messy), and are terrified of Adalyn (counterproductive), and are nine-year-old kids. To make things worse, also in town is Cameron Caldani, goalkeeping prodigy whose presence is somewhat of a mystery. Cam is the perfect candidate to help Adalyn, but after one very unfortunate first encounter involving a rooster, Cam's leg, and Adalyn's bumper, he's also set on running her out of town. But banishment is not an option for Adalyn. Not again. Helping this ragtag children's team is her road to redemption, and she is playing the long game. With or without Cam's help.